2018
DOI: 10.1016/j.jfoodeng.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Menthol/cyclodextrin inclusion complex nanofibers: Enhanced water-solubility and high-temperature stability of menthol

Abstract: Cyclodextrins are capable of forming non-covalent host-guest inclusion complexation with variety of molecules in order to enhance water-solubility and thermal stability of such hydrophobic and volatile molecules. Menthol, an efficient antibacterial and flavour/fragrance agent, is used in various applications like food, pharmacy, cosmetics, however, its low water-solubility and high volatility somewhat limit its application. In this study, menthol/cyclodextrin-inclusion complex (menthol/CD-IC) was formed in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 41 publications
4
47
0
Order By: Relevance
“…To reveal the mechanism of inclusion complex, ab initio calculations based on density functional J Mater Sci (2018) 53:15837-15849 theory were done according to our previous studies [21,23].…”
Section: Measurements and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…To reveal the mechanism of inclusion complex, ab initio calculations based on density functional J Mater Sci (2018) 53:15837-15849 theory were done according to our previous studies [21,23].…”
Section: Measurements and Characterizationmentioning
confidence: 99%
“…Nonetheless, in our previous studies, uniform fibers from cyclodextrins have been successfully electrospun since cyclodextrin molecules can form aggregates via intermolecular hydrogen bonding in their highly concentrated solutions which results in formation of continuous jet without breaking up [11,12]. Moreover, in our recent studies, it has been shown that the fabrication of functional fibers from cyclodextrin inclusion complexes (CD-IC) with food additives and antibacterial substances is also possible [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of such CD aggregates prevents the breakage of the jet during electrospinning, and therefore bead-free uniform NFs can be electrospun from pure CD. 17−19 Furthermore, electrospun NFs from a variety of CD-ICs with food flavors and essential oils such as vanillin, 20 vitamin E, 21 eugenol, 22 menthol, 23 thymol, 24 and carvacrol 25 were also produced successfully.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The applicability of encapsulation to MPEO was previously researched with maltodextrin [127], modified starches [128,129], and gelatin/gum Arabic [130] as core materials. Additionally, menthol was encapsulated in cyclodextrin [131]. It was shown that encapsulation was effective for retaining of PMEO and its sustaining release [128][129][130].…”
Section: Formulations Of Menthol Mint Essential Oils In Agriculture-lmentioning
confidence: 99%